Parenting Patterns of Blind Parents in Fostering the Independence of Visually Impaired Children - Wijaya, Dwico Sandi; Maisuhetni, Maisuhetni; Andayani, Ance (Ensiklopedia: Jurnal Pendidikan dan Inovasi Pembelajaran Saburai, 2025)
fostering the independence of their visually impaired children. Using a qualitative descriptive approach with a case study method, data were collected through in-depth interviews, direct observation, and documentation involving three blind parents and their children. The results show that blind parents implement a democratic parenting style, using strategies based on verbal communication, daily routines, and gradual life skills training. Despite physical limitations and environmental barriers, the parents were still able to foster their children’s independence in areas such as personal hygiene, mobility, and simple decision-making. Social support from spouses, extended family, and educational institutions further reinforced the effectiveness of the parenting strategies used. This study highlights that disability does not hinder parenting capacity, and emphasizes the importance of collaboration between family and the surrounding environment to optimally support the development of children with visual impairments.